2022
DOI: 10.1371/journal.pmed.1003949
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a brief group behavioral intervention for common mental disorders in Syrian refugees in Jordan: A randomized controlled trial

Abstract: Background Common mental disorders are frequently experienced by refugees. This study evaluates the impact of a brief, lay provider delivered group-based psychological intervention [Group Problem Management Plus (gPM+)] on the mental health of refugees in a camp, as well as on parenting behavior and children’s mental health. Methods and findings In this single-blind, parallel, randomized controlled trial, 410 adult Syrian refugees (300 females, 110 males) in Azraq Refugee Camp (Jordan) were identified throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
44
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 40 publications
(51 citation statements)
references
References 56 publications
(69 reference statements)
1
44
0
Order By: Relevance
“…Not only do primary health care workers within refugee contexts need to be better equipped to address common mental health conditions (e.g., depression, anxiety, PTSD, and substance use), but more also needs to be done to provide treatment and support outside of health facilities. As mentioned previously, the recent surge in research around “scalable psychological interventions” in humanitarian settings provides increasing opportunities to administer brief, evidence-based psychological therapies that can be delivered by trained and supervised non-specialist providers, including refugees themselves [ 49 – 51 , 64 ]. Again, efforts towards this action are ongoing.…”
Section: Discussionmentioning
confidence: 99%
“…Not only do primary health care workers within refugee contexts need to be better equipped to address common mental health conditions (e.g., depression, anxiety, PTSD, and substance use), but more also needs to be done to provide treatment and support outside of health facilities. As mentioned previously, the recent surge in research around “scalable psychological interventions” in humanitarian settings provides increasing opportunities to administer brief, evidence-based psychological therapies that can be delivered by trained and supervised non-specialist providers, including refugees themselves [ 49 – 51 , 64 ]. Again, efforts towards this action are ongoing.…”
Section: Discussionmentioning
confidence: 99%
“…There were 1377 caravans approached during screen, 624 refugees agreed to be screened, of which 462 met entry criteria and 410 proceeded to randomisation (204 randomised to gPM + and 206 to EUC). Full details of the participants are reported in the prior report of the study (Bryant et al ., 2022 ) and reported in online Supplementary Tables 2 and 3. The mean age of participants was 40.03 years ( s.d.…”
Section: Resultsmentioning
confidence: 99%
“…This intervention teaches skills in arousal reduction, problem management, behavioural activation and accessing social support across five sessions (Dawson et al ., 2015 ). PM + delivered in individual (Rahman et al ., 2016 ; Bryant et al ., 2017 ) and group (Rahman et al ., 2019 ; Jordans et al ., 2021 ; Bryant et al , 2022 ) formats has been shown to be effective in reducing common mental disorders.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The intervention comprises of evidence-based techniques including stress management, problem solving, behavioral activation, and social support enhancement [14]. Developed to be delivered by lay personnel involving those without specialist mental health qualifications, PM + has been shown to reduce mental distress and increase wellbeing in those exposed to adversity and crises across diverse demographic groups [15][16][17][18][19]. Recently, an adapted version of this program was delivered via video teleconferencing, Coping with COVID (CWC) was found to reduce worry, anhedonia, and contamination fears arising during the pandemic [20].…”
Section: Introductionmentioning
confidence: 99%